Expression of the forkhead transcription factor FOXP1 is associated both with hypoxia inducible factors (HIFs) and the androgen receptor in prostate cancer but is not directly regulated by androgens or hypoxia. - Banham, A; Boddy, J; Launchbury, R; Han, C; Turley, H; Malone, P; Harris, A; Fox, S (2007)
BACKGROUND: FOXP1 is a member of the winged helix or forkhead transcription factors. Recent studies have indicated possible roles for FOXP1 as a candidate tumor suppressor gene and a potential estrogen receptor (ER) co-regulator in the development of breast cancer. This study investigated whether FOXP1 has a similar relationship to the androgen receptor (AR) in prostate cancer and how these factors relate to the presence of hypoxia. METHODS: FOXP1, the AR and various hypoxia-regulated proteins (HIF-1alpha, HIF-2alpha, and VEGF) were measured with immunohistochemistry using a tissue microarray constructed from 167 archival radical prostatectomies. Statistical analyses compared the co-expression of these factors both with each other and conventional parameters including patient age, pre-operative prostate specific antigen (PSA), post-operative Gleason score, capsular invasion, surgical margin status, tumor volume, and PSA recurrence. The influence of hypoxia, dihydrotestosterone, and the AR blocker Casodex was investigated in prostate cell lines VCaP and LNCaP in vitro. RESULTS: Expression of nuclear FOXP1 was significantly positively correlated with AR (P = 0.0001), hypoxia inducible factor 1alpha (HIF-1alpha) (P = 0.01), HIF-2alpha (P = 0.0001), and vascular endothelial growth factor (VEGF) (P = 0.007) expression. A positive significant relationship was also identified with the post-operative Gleason score (P = 0.03) but not with the other variables, including PSA recurrence (P > 0.05). There was no significant change in expression in FOXP1 protein levels under conditions of hypoxia (0.1%), dihydrotestosterone stimulation (10 or 100 nM), or androgen blockade with Casodex (1, 10, or 50 microM). CONCLUSION: These findings suggest that there may be a hormonal and hypoxia independent regulatory mechanism coordinating the expression of HIFs, the AR, and FOXP1 in prostate tumors.